A novel apoA‐I mimetic peptide suppresses atherosclerosis by promoting physiological HDL function in apoE−/− mice. (9th September 2020) - Gou, Sanhu; Wang, Li; Zhong, Chao; Chen, Xinyue; Ouyang, Xu; Li, Beibei; Bao, Guangjun; Liu, Hui; Zhang, Yun; Ni, Jingman
Abstract : Background and Purpose: Apolipoprotein A‐I (apoA‐I) mimetic peptides (AAMPs) are short peptides that can mimic the physiological effects of apoA‐I, including the suppression of atherosclerosis by reversely transporting peripheral cholesterol to the liver. As the hydrophobicity of apoA‐I is considered important for its lipid transport, novel AAMPs were designed and synthesized in this study by gradually increasing the hydrophobicity of the parent peptide, and their anti‐atherosclerotic effects were tested. Experimental Approach: Seventeen new AAMPs (P1–P17) with incrementally increased hydrophobicity were designed and synthesized by replacing the amino acids 221–240 of apoA‐I (VLESFKVSFLSALEEYTKKL). Their effects on cholesterol efflux were evaluated. Their cytotoxicity and haemolytic activity were also measured. The in vitro mechanism of the action of the new peptides was explored. Adult apolipoprotein E −/− mice were used to evaluate the anti‐atherosclerotic activity of the best candidate, and the mechanistic basis of its anti‐atherosclerotic effects was explored. Key Results: Seventeen new AAMPs (P1–P17) were synthesized, and their cholesterol efflux activity and cytotoxicity were closely related to their hydrophobicity. P12 (FLEKLKELLEHLKELLTKLL) was the best candidate and most strongly promoted cholesterol efflux among the non‐toxic peptides (P1–P12). With its phospholipid affinity, P12 facilitated cholesterol transport through the ATP‐binding cassette transporter A1. In vivo, P12 exhibited prominent anti‐atherosclerotic activity via coupling with HDL. Conclusion and Implications: P12 featured adequate hydrophobicity, which ensured its efficient binding with cytomembrane phospholipids, cholesterol and HDL, and provided a basis for its ability to reversely transport cholesterol and treat atherosclerosis. Abstract :